Sobre intertextualidades estritas e amplas - Carvalho, Ana Paula Lima de (2018)
This study proposes a theoretical reflection on the textual-discursive phenomenon of transtextualities described by Genette ([1982] 2010), rethinking and redistributing them into two large groups, called intertextualities in broad sense and intertextualities in strict sense. Its beginning is the analytical framework of this author, who analyzed the relations of dialogue between texts, genres and styles, based on structural and functional criteria, to present a resizing of the categories, in order to account for describing, from the point of view of Textual Linguistics, the manifested occurrences also in multisemiotic texts and of different discursive domains, not only literary ones. The delimitation of the proposal is basically due to the identification of gaps in previous research, from which the hypotheses have been elaborated, in order to try to establish classification criteria that take into account the multisemiotic reality that marks most of the texts that circulate socially. The study argues that intertextualities are constitutionally distinguished into two broad categories: strict and broad. The first one covers the cases in which it is possible to accurately retrieve the original text (s) to which it was appealed, which were subdivided into: copresence, transposition, parody and metatextuality. The second, which refers to the relations established between a text and a set of texts, includes cases of imitation (gender and author) and broad allusion.